Neonatal White Matter Maturation Is Associated With Infant Language Development - Sket, Georgina M.; Overfeld, Judith; Styner, Martin; Gilmore, John H.; Entringer, Sonja; Wadhwa, Pathik D.; Rasmussen, Jerod M.; Buss, Claudia (Frontiers in Human Neuroscience, 2019)
Background: While neonates have no sophisticated language skills, the neural basis for acquiring this function is assumed to already be present at birth. Receptive language is measurable by 6 months age and meaningful speech production by 10-18 months of age. Fiber tracts supporting language processing include the corpus callosum (CC), which plays a key role in the hemispheric lateralization of language, the left arcuate fasciculus (AF), which is associated with syntactic processing, and the right AF, which plays a role in prosody and semantics. We examined if neonatal maturation of these fiber tracts is associated with receptive language development at 12 months of age. Methods: Diffusion weighted imaging (DWI) was performed in 86 infants at 26.6 ± 12.2 days post birth. Receptive language was assessed via the MacArthur-Bates Communicative Development Inventory at 12 months of age. Tract-based fractional anisotropy (FA) was determined using the NA-MIC atlas-based fiber analysis toolkit. Associations between neonatal regional FA, adjusted for gestational age at birth and age at scan, and language development at 12 months of age were tested using ANOVA models. Results: After multiple comparisons correction, higher neonatal FA was positively associated with receptive language at 12 months of age within the genu (p<0.001), rostrum (p<0.001), and tapetum (p<0.001) of the CC and the left fronto-parietal AF (p=0.008). No significant clusters were found in the right AF. Conclusions: Microstructural development of the CC and the AF in the newborn is associated with receptive language at 12 months of age, demonstrating that interindividual variation in white matter microstructure is relevant for later language development, and indicating that the neural foundation for language processing is laid well ahead of the majority of language acquisition. This suggests some origins of impaired language development may lie in the intrauterine and potentially neonatal period of life. Understanding how interindividual differences in neonatal brain maturity relate to the acquisition of function, particularly during early development when the brain is in an unparalleled window of plasticity, is key to identifying opportunities for harnessing neuroplasticity in health and disease.